Horizontal drilling drainage as a preventive measure for water induced landslide risk reduction: A case study from Sindhuli Road, Section I, Nepa (Journal of Nepal Geological Society, 2018)
Nepal is a mountainous country which covers about 83% area of the Higher Himalaya, mountain and hills with rugged topography and highly tectonic geology. Most of those areas are prone to sediment related water induced disasters such as slope failure, debris flow, and landslide which are triggered due to torrential rainfall during the monsoon rainy season, and that causes the loss of lives and properties, infrastructures and environmental degradation each year. The annual rainfall ranges from 2000 to 3000 mm (in the Central Region of Nepal). The natural disasters cannot be prevented completely but efforts can be made for mitigating the impact of the disasters. Among the mitigation measures of water induced landslide disasters, the Horizontal Drilling Drainage Technology is one of the most effective counter measures of landslide risk reduction. The main purpose of this technology is to release the pore water pressure in the landslide mass by reducing the groundwater level. The landslide disaster prone Kamala Mai village area lies along the Sindhuli road section I, the National Highway, in Sindhuli District, Nepal which was generating subsidence and creeping of the road each year since many years back. This method was applied in the Sindhuli road Section I, Chanaige 29+300, Kamala Mai Village area. The result obtained from the application of the method shows an effective achievement to the Sindhuli road stability and the road users as well. Recommendation has been made to replicate the technology in other places of the country also in similar environment.